Integrated Framework for Manufacturing, Design, and Monitoring of Composite-Bonded Joints: An Overview of the Results of the IDEA Project (MOST) - Marino Quaresimin; Paolo Andrea Carraro; Federico Lamon; Silvia Giovanna Avataneo; Matteo Basso; Andrea Merulla; Umberto Galietti; Ester D’Accardi; Davide Palumbo; Massimiliano De Agostinis; Mattia Mele; Monica Ferraris; et al. (Engineering Proceedings, 2025)
The IDEA project, developed in the frame of MOST—National Centre for Sustainable Mobility—addressed the growing need for reliable bonded joints in fibre-reinforced polymer composite structures used in transportation. Purely bonded joints are preferred for their lightweight and cost-efficient properties, but contamination and defect detection issues often make them unreliable. To solve this, the project developed innovative surface treatments, a methodology for the safe, optimized design of bonded joints, and structural health monitoring solutions, viable for real-time assessment. These advancements aim to increase the reliability and safety of bonded connections, helping industries adopt lighter, purely bonded joints over heavier, hybrid bonded/bolted options.